Knowledge Acquisition in Information System Development: A Case Study of System Developers in an International Bank1. (20th January 2016) - White, Gareth R.T.; Parry, Glenn Charles; Puckering, Aneka
Abstract : System developers quickly acquire knowledge of the benefits and limitations of system development approaches and this knowledge enables them to adopt or adapt methodologies according to the scope and scale of projects.